Spotting of Distribution Voltage Quality Annoyance in Distribution System - et al., S.Sudha Rani (International Journal of Advanced Science and Technology, 2019)
The most concerning issue for power engineers is power quality terms. Dynamic voltage restorer (DVR) is power quality enhancer and infuses voltage to distribution feeder in series to mitigate sag/swell. The study of detection and mitigation of voltage sag/swell is presented in this paper. The sag/swell issue is mitigated using SRF (Synchronous Reference Frame Theory) controlled DVR (Dynamic Voltage Restorer). This paper investigates the DVR controlled with SRF control methodology to compensate for sag/swell in different phase voltages is tested and Simulation analysis is carried out using MATLAB\SIMULINK .